Response of activated sludge to high concentration salt - New, Shu Wei. (2009)
Having seawater flushing system in Singapore will result in high salt content in the sewage. Problems may arise due to the high salinity in the wastewater treatment system particularly the biological processes. It is hypothesized that high salt concentration will affect the microorganisms; therefore, inhabit the pollutants removal efficiency in the activated sludge process. This study investigated performance of the activated sludge at different concentrations and a fixed NaCl concentration at 15 g/L. The study is thus being carried out to look into the performance of activated sludge process with salinity. The experiment was performed by introducing salt, NaCl, directly into batch reactors containing activated sludge and aeration was allowed over a period of 4 hours. The batch reactors were prepared such that it contained activated sludge in the concentrations of 250 mg/L, 500 mg/L, 750 mg/L, 150 0mg/L, 2000 mg/L and 3000 mg/L and the NaCl dosed in each reactor was fixed to 15g/L. At 0 hour, 2nd hour and 4th hour, the dissolved oxygen (DO) to determine the specific oxygen uptake rate (SOUR) of the sludge were recorded. The morphology of bacteria was examined and sludge volume index (SVI) was performed, to observe the settling characteristics of activated sludge at varying salt concentrations. The results obtained from the study shows that the TOC removal efficiencies for 4 hours were over 95% and can be considered good in the presence of 15 g/L of NaCl except for 250 mg/L sludge concentration. The observations also revealed that 750mg/L sludge batch reactors had higher TOC removal and more MLSS growth at NaCl concentration of 15g/L. In addition, the SVI for 750 mg/L sludge concentration lies between 50 to 100ml/g implying relatively good settling. This may be suggesting that 750mg/L of initial sludge concentration was probably the optimum sludge concentration. The results also revealed that the overall observed yields were reasonably good except for the 250mg/L sludge concentration. This might be suggesting that at 15g/L NaCl, the impact of the salt to the microorganism may not be as great to affect the overall performance of the activated sludge.